Political Propaganda Of 2024 Election In Dirty Vote Movie (Van Dijk's Critical Discourse Analysis) - Khumaeroh, Eroh; Tomi Saputra, Faisal; Irianti, Een (Center of Language and Cultural Studies, 2024)
Abstract The development of movies in Indonesia is very diverse, ranging from fiction to documentaries. In 2024, Indonesia was shocked by one of the documentary films that was beyond people's expectations. The movie was titled